Self-regulated learning of the forehand top spin in table tennis - Bund, A. (Journal of Sports Sciences, 2006)
Introduction: The effectiveness of self-regulation, or self-control, for learning has been demonstrated in the verbal or cognitive learning for a number of years (for an overview see Boekaerts et al., 2000, Handbook of self-regulation, San Diego a.o.: Academic Press). More recently, researchers have also begun to examine the effect of self-regulation on motor skill learning. In general, these studies show that self-regulation during the learning process can lead to better motor performance.